Reflection on the dialogue between the Greeks - Vélez Upegui, Mauricio (Estudios de Filosofía, 2004)
Through an observation of Rafael Sanzio’s fresco entitled Stanza della Segnatura, this text attempts to carry out a reflection on the practice of dialogue among ancient Greeks. This reflection goes through an urge of characterization of the genre known as "Socratic dialogue". It arrives to a known, though not irrelevant conclusion: a dialogue, strictly speaking, never ends. At the end, a series of correspondences between the meaning of the act of contemplation or the act of reception in a subject that, far from Greek time and space, acts as an observer or reader of a human work.